TEACHING AND IMPROVING FOOTBALL TECHNIQUES OF 13–14-YEAR-OLD SCHOOLCHILDREN ON THE BASIS OF DEVELOPING LEADING PHYSICAL QUALITIES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
The article examines the methodological foundations for teaching and improving football techniques among 13–14-year-old schoolchildren through the targeted development of leading physical qualities. Special attention is given to the integration of speed, strength, endurance, agility, and coordination into the technical training process. The study justifies that a comprehensive and systematic approach significantly enhances technical performance and overall athletic development in young football players.